Feeling the clunk: Managing and attributing uncertainty in screening for developmental dysplasia of the hip in infancy - Sarah Milton; Gill Gilworth; Andreas Roposch; Judith Green (Elsevier, 2022)
The management of uncertainty in clinical practice has been an enduring topic of sociological scholarship. However, little of this addresses how uncertainty and non-knowledge are attributed to the self and other actors. We take the example of checking for developmental dysplasia of the hip (DDH), part of infant screening in UK primary care, to examine the 'double contingency' of attributions of uncertainty and ignorance. Our data come from interviews with parents and General Practitioners (GPs), and observations of the six-week check conducted as part of a study to develop a checklist to aid GPs' diagnostic and referral decisions. Parents' pervasive uncertainties about managing with a new-born infant place them in a trusting relation to biomedicine, in which knowledge about infant hips is delegated to the clinical team: most described themselves as not-knowing about DDH. GPs focus on the uncertainties of applying sensory and experiential knowledge of infant bodies, in a consultation with more diffuse aims than screening for DDH. A prototype checklist, developed by orthopaedic specialists, was an explicit attempt to reduce uncertainty around thresholds for referral. However, using the checklist surfaced multiple logics of uncertainty. It also surfaced attributions of uncertainty and non-knowledge to other actors: orthopaedic specialists' assumptions about GPs' uncertain technical knowledge; GPs' assumptions about orthopaedic specialists' ignorance of the primary care setting; and clinicians' assumptions about the role of parental ignorance. This 'double contingency' of attributions of other actors' non-knowledge is a salient additional dimension to the uncertainty that infuses biomedical practice.